A Case Study Of Seksum Technology (Johor) Sdn Bhd - Yap, Ming Cur (2008)
Seksun Technology is one of the market leaders in Johor Bahru metal stamping industry. The focus of this study is to identify Seksun Technology's target market and strategies which can improve the organization in terms of internal operation and external customers' satisfactions. This study is conducted with the objectives to identify and recognize Seksun's strengths and opportunities with its core competencies in order to achieve the sustainability growth.